Vici syndrome with pathogenic homozygous EPG5 gene mutation: A case report and literature review. Issue 43 (23rd October 2020) - Abidi, Kamal T.; Kamal, Naglaa M.; Bakkar, Ayman A.; Almarri, Saad; Abdullah, Rehab; Alsufyani, Maram; Alharbi, Arwa
Abstract: Rationale: Vici syndrome (VICIS) is a rare, autosomal recessive neurodevelopmental disorder with multisystem involvement characterized by agenesis of the corpus callosum, congenital cataracts, cardiomyopathy, combined immunodeficiency, significant developmental delay, and hypopigmentation and in some cases loss of hearing. It is caused by mutations in Ectopic P-granules protein 5 gene, which is responsible for regulating autophagy activity. Patient concern: We report a 6-month-old Saudi female patient who was the second-born baby of first cousins. She was born by normal spontaneous vertex vaginal delivery. Parents noticed that she had global developmental delay and recurrent hospital admissions due to chest infections. Diagnosis: Brain magnetic resonance imaging showed brain atrophy with corpus callosum agenesis. Ophthalmology examination revealed bilateral congenital cataract. Molecular genetic testing identified the pathogenic homozygous variant c.4751T>A p. (Leu1584*) on exon 27 of the EPG5 gene and confirmed the diagnosis of Vici syndrome. Interventions: Supportive multidisciplinary care plan was initiated to this untreatable syndrome. Outcomes: The patient died at the age of 6 months due to sepsis with uncompensated septic shock. Lessons: VICIS is a rare untreatable disorder with worldwide distribution. High index of suspicion is needed to diagnose it and family genetic counselling is crucial.